Nanohybrids as Protein-Polymer Conjugate Multimodal Therapeutics - Kiran, Pallavi; Khan, Amreen; Neekhra, Suditi; Pallod, Shubham; Srivastava, Rohit (Frontiers in Medical Technology, 2021)
Protein therapeutic formulations are being widely explored as multifunctional nanotherapeutics. Challenges in ensuring susceptibility and efficacy of nanoformulation still prevail owing to various interactions with biological fluids before reaching the target site. Smart polymers with the capability of masking drugs, ease of chemical modification, and multi-stimuli responsiveness can assist controlled delivery. Active moiety like therapeutic protein has advent as an important biological manifest with the diverse medicinal prospect. The delivery of proteins and peptides with high target specificity has however been tedious, due to their tendency of aggregate formation in different environmental conditions. Proteins due to high chemical reactivity and poor bioavailability are being researched widely in the field of nanomedicine. Clinically, multiple nano-based formulations have been explored for delivering protein with different carrier systems. A biocompatible and non-toxic polymer-based delivery system serves to tailor the polymer or drug better. Polymer not only aid to reach the target site but also responsible for proper stearic orientation of protein thus protecting from internal hindrances. Polymers have been shown to conjugate with protein through covalent linkage rendering stability and enhancing therapeutic efficacy prominently when dealing with the systemic route. Here, we present the recent developments in polymer-protein/drug-linked systems. We incline to address questions by assessing the properties of the conjugate system and optimized delivery approaches. Since, thorough characterization is the key aspect for technology to enter into the market, correlating the laboratory research with commercially available formulations will also be presented in the review. Examining characteristics including morphology, surface properties, and functionalization we will expand different hybrid applications from biomaterial stance applied in in-vivo complex biological conditions. Further, exploring understanding related to design criteria and strategies for polymer-protein smart nanomedicines with their potential prophylactic theranostic applications. Overall, we intend to highlight protein-drug delivery through multifunctional smart polymers.